The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fped.2021.576916
|View full text |Cite
|
Sign up to set email alerts
|

Keshan Disease: A Potentially Fatal Endemic Cardiomyopathy in Remote Mountains of China

Abstract: Keshan disease (KD) as an endemic, highly lethal cardiomyopathy, first reported in northeast China's Keshan County in 1935. The clinical manifestations of patients with KD include primarily congestive heart failure, acute heart failure, and cardiac arrhythmia. Even though some possible etiologies, such as viral infection, fungal infection, microelement deficiency, and malnutrition, have been reported, the exact causes of KD remain poorly known. The endemic areas where KD is found are remote and rural, and many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 116 publications
0
24
0
Order By: Relevance
“…Supporting this hypothesis, administration of oral Se reversed Se deficiency and improved outcomes of KD [ 25 , 26 ]. Although there is some debate about whether Se deficiency is the primary cause of KD as there are several additional underlying causes, it remains until now the most convincing possibility [ 1 , 26 ].…”
Section: The Relationship Between Se Deficiency and Cardiovascular Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting this hypothesis, administration of oral Se reversed Se deficiency and improved outcomes of KD [ 25 , 26 ]. Although there is some debate about whether Se deficiency is the primary cause of KD as there are several additional underlying causes, it remains until now the most convincing possibility [ 1 , 26 ].…”
Section: The Relationship Between Se Deficiency and Cardiovascular Healthmentioning
confidence: 99%
“…Selenium (Se) is an essential trace element necessary for a variety of biological functions in animals, including cardiovascular function. Se deficiency has been linked to different cardiovascular diseases, including cardiomyopathies such as Keshan’s disease (KD) [ 1 , 2 ], heart failure [ 3 , 4 ], and myocardial infarction [ 5 ]. Although there has been increasing evidence of the importance of Se for optimal cardiovascular function, the role of Se in cardiovascular syndromes, particularly under dietary Se deficiency, remains only partially understood.…”
Section: Introductionmentioning
confidence: 99%
“…In Zambia, cardiomyopathy accounts for 75% morbidity and 30% mortality of all cases seen at the Adult Medicine Hospital in Lusaka (University Teaching Hospital Adult medicine records). Se deficiency is known to be involved in Keshan disease, a severe form of cardiomyopathy endemic to China [ 33 ], and a study in Nigeria showed that Se levels of less than 70 μg/L was a risk factor for development of peripartum cardiomyopathy [ 34 ]. Given that 99% of pregnant women in our study had plasma Se < 40 μg/L, this is a point of particular concern.…”
Section: Discussionmentioning
confidence: 99%
“…SeMet is, however, the main organic form of Se in plants, while SeCys is dominant in animal based-food [106]. Se supplemented in the form of SeMet to the human diet was reported to promote the synthesis of defensive proteins and antioxidant enzymes present on the mucosal surface, which is a physical barrier that prevents the entry of pathogens into the body [107]. After intake, SeMet is absorbed in the intestine through transporters for methionine and can then be metabolized in two different ways; it either directly participates in the protein synthesis, or is converted to SeCys, which is further metabolized with the production of selenide.…”
Section: Inorganic and Organic Se Species Functioning As Antioxidants And Immune Agentsmentioning
confidence: 99%
“…This process was at least reported for coxsackievirus B3 (CVB3), influenza virus type A /Bangkok/1/79 (H3N2), influenza H1N1, human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS), polio, hepatitis B and C, and hantavirus [28]. Keshan disease, for instance, arises when CVB3 mutates to a more virulent strain in a host deficient in Se [87,107,138,139]. Unfortunately, RNA viral mutations are reported to be faster, more frequent, and long-lasting in Se-flawed hosts [140].…”
Section: Roles Of Selenoproteins In Viral Diseasesmentioning
confidence: 99%